2015
DOI: 10.18632/oncoscience.152
|View full text |Cite
|
Sign up to set email alerts
|

The DAXX co-repressor is directly recruited to active regulatory elements genome-wide to regulate autophagy programs in a model of human prostate cancer

Abstract: While carcinoma of the prostate is the second most common cause of cancer death in the US, current methods and markers used to predict prostate cancer (PCa) outcome are inadequate. This study was aimed at understanding the genome-wide binding and regulatory role of the DAXX transcriptional repressor, recently implicated in PCa. ChIP-Seq analysis of genome-wide distribution of DAXX in PC3 cells revealed over 59,000 DAXX binding sites, found at regulatory enhancers and promoters. ChIP-Seq analysis of DNA methylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 30 publications
(41 reference statements)
4
27
0
Order By: Relevance
“…10B) cannot proceed. Although ULK1 has multiple targets in cell signaling and regulates other cellular processes besides autophagy (55), additional support that autophagy is indeed a mechanism by which DAXX affects tumorigenesis in PCa comes through our use of the ATG5-deficient cell line, DU145 (this study) and ChIP-seq/RNA-seq analyses (13). DAXX ChIP-seq peaks were found close to the TSSs of autophagy genes, and genes increased by DAXX K/D included those involved in autophagy.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…10B) cannot proceed. Although ULK1 has multiple targets in cell signaling and regulates other cellular processes besides autophagy (55), additional support that autophagy is indeed a mechanism by which DAXX affects tumorigenesis in PCa comes through our use of the ATG5-deficient cell line, DU145 (this study) and ChIP-seq/RNA-seq analyses (13). DAXX ChIP-seq peaks were found close to the TSSs of autophagy genes, and genes increased by DAXX K/D included those involved in autophagy.…”
Section: Discussionmentioning
confidence: 84%
“…DAXX ChIP-seq peaks were found close to the TSSs of autophagy genes, and genes increased by DAXX K/D included those involved in autophagy. Furthermore, RNA-seq showed that DAXX was inversely correlated with the expression of positive regulators of autophagy (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ChIPsequencing analyses showed in a prostate cancer cell model that the co-repressor DAXX (death domain associated protein) colocalized with DNMT1 near the TSS (transcriptional start site) of several ATG-related genes including ULK1 and DAPK3 (death-associated protein kinase 3) [5]. Since DAXX has already been shown to specifically recruit DNMTs on specific target promoters, these data strongly suggested that DAXX may actively mediate a methylation-dependent silencing of ATG genes [6].…”
Section: Molecular Mechanisms Inhibiting Atg Gene Expression Via Dna mentioning
confidence: 90%